Advances in entomological laser radar. Issue 21 (28th October 2019) - Brydegaard, Mikkel; Jansson, Samuel
Abstract : During the past decade, the authors have developed and applied optical remote sensing instrumentation for in situ remote surveillance and quantification of the aerofauna. The sparse structure of aerofauna makes optical focusing challenging, but the authors solved this issue through applying the century old Scheimpflug condition. With this approach, the authors have managed to reduce size, cost and complexity of atmospheric lidars and accomplished an effective tool for ecological entomology capable of counting thousands of insects per hour. Due to the high sensitivity and resolution in time and space, the authors can retrieve target modulation signatures in the kHz range for target classification purposes. As opposed to the cm waves in entomological radar, the authors rely on near infrared (IR) light ∼1 μm. This allows superior beam quality, negligible ground clutter and applications close over ground or within vegetation structure. Near IR light can assess both molecular and microstructural properties of the target through differential absorption and depolarisation. Here the authors give the background of entomological lidar, summarise the authors' recent progress and put it in context with contemporary work. The authors outline applications, ongoing activities and state of the art. The authors discuss future prospects and challenges.